2014
DOI: 10.1093/jxb/eru308
|View full text |Cite
|
Sign up to set email alerts
|

Proline-rich protein-like PRPL1 controls elongation of root hairs in Arabidopsis thaliana

Abstract: The synthesis and composition of cell walls is dynamically adapted in response to many developmental and environmental signals. In this respect, cell wall proteins involved in controlling cell elongation are critical for cell development. Transcriptome analysis identified a gene in Arabidopsis thaliana, which was named proline-rich protein-like, AtPRPL1, based on sequence similarities from a phylogenetic analysis. The most resemblance was found to AtPRP1 and AtPRP3 from Arabidopsis, which are known to be invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 70 publications
(87 reference statements)
0
29
0
1
Order By: Relevance
“…A putative scenario might be that the high ploidy level is required for an increased metabolic output required for tip outgrowth. Root hairs have been found to express unique cell expansion and cell wall-modifying enzymes, including specific expansins and pectin-interacting proline-rich proteins (Bernhardt and Tierney, 2000;Boron et al, 2014;Cho and Cosgrove, 2002;Vissenberg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…A putative scenario might be that the high ploidy level is required for an increased metabolic output required for tip outgrowth. Root hairs have been found to express unique cell expansion and cell wall-modifying enzymes, including specific expansins and pectin-interacting proline-rich proteins (Bernhardt and Tierney, 2000;Boron et al, 2014;Cho and Cosgrove, 2002;Vissenberg et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the gene At5G05500 was co-expressed with many root hair-related genes, indicating a possible role of this gene in root hair development. Indeed, a recent study showed that At5G05500 shared high similarities with AtPRP1 and At-PRP3, and analysis of knock-out or overexpression lines indicated that At5G05500 was involved in root hair elongation process [65]. In addition, this sub-cluster contained several function unannotated genes that are worthy of further research.…”
Section: Common Elements Of Root Hair Morphogenesis In Plantsmentioning
confidence: 94%
“…Under normal conditions, PRPs are constitutively expressed in roots and vegetative tissues (Bouton et al 2005, Peng et al 2015. The PRPL1 gene of Arabidopsis is peculiarly expressed in root hairs and triggers their elongation (Boron et al 2014). Involvement of PRPs in cell elongation is further supported by overexpression of the HyPRP gene in tobacco BY-2 cell lines where calli size increases in suspension culture as well as on solid media (Dvorakova et al 2012).…”
Section: Developmental Functions Of Prpsmentioning
confidence: 99%